2014
DOI: 10.1039/c3cp54833c
|View full text |Cite
|
Sign up to set email alerts
|

A mutarotation mechanism based on dual proton exchange in the amorphous d-glucose

Abstract: It is a well known fact that carbohydrates have unusual chemical and physical properties when they approach the glassy state during the cooling process. Differences between sugar aqueous solutions and their pure anhydrous states are caused mainly by the different intermolecular interactions related to the different hydrogen bond patterns. The mutarotation, a specific reaction in the saccharides, was recently investigated in the supercooled liquid and the glassy state of D-glucose. It was shown that the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Having in mind the results of inter- and intramolecular investigations performed with the use of BDS and FTIR techniques, we decided to examine experimentally the progress of mutarotation in the supercooled state, both above and below the T c . Recently, many articles on the monitoring of mutarotation in the vicinity of the glass transition temperature with the use of dielectric spectroscopy have been published 21 24 , 26 , 36 . In these papers, it was reported that the changes in dielectric spectra get much smaller and are barely detectable with increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Having in mind the results of inter- and intramolecular investigations performed with the use of BDS and FTIR techniques, we decided to examine experimentally the progress of mutarotation in the supercooled state, both above and below the T c . Recently, many articles on the monitoring of mutarotation in the vicinity of the glass transition temperature with the use of dielectric spectroscopy have been published 21 24 , 26 , 36 . In these papers, it was reported that the changes in dielectric spectra get much smaller and are barely detectable with increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, they also suggested that in the supercooled liquid phase (above T g ), mutarotation initiates via mutual proton transfer between two neighboring sugar molecules. 28 From the perspective of the above discussion, we expect that the application of pressure could enhance the degree of cooperative motion in a supercooled state near glass transition and eventually translate a stronger sugar-sugar interaction which will support intermolecular proton transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In solution or in the liquid state, mutarotation is generally fast and an equilibrium tautomeric composition is rapidly reached. In the amorphous solid state, mutarotation has been found to require a much higher activation energy, so mutarotation kinetics is quite slower. , While there is almost no molecular mobility in crystals, Tombari et al have postulated that mutarotation can also occur in this ordered physical form through the mediation of vacancies and defects. It then causes local amorphizations, which could ultimately lead to the liquefaction of sugars well below their known melting points .…”
Section: Introductionmentioning
confidence: 99%